Adaptive routing and wavelength assignment method based on SDN - Zhongnan ZHAO; Jian WANG; Hongwei GUO (Tongxin xuebao)
Routing and wavelength assignment is an important resource allocation method of all-optical network.Aiming at the problem of traditional method combined with the new architecture,an adaptive multi-objective routing and wavelength assignment method based on SDN was proposed,which could realize the allocation of link resources of all-optical network through self-regulation.Based on the SDN service function chain model,service scheduling time and link service quality were taken as the scheduling objective,routing and wavelength assignment problem was constructed as the 0-1 integer programming problem,meanwhile,binary hybrid topology particle swarm optimization algorithm was used to optimize the network resources for optimal scheduling.The simulation results show that the proposed method is superior to the traditional classical algorithms in the test of recovery time,blocking rate and resource utilization.